Analisis Kebutuhan Parkir Eksisting Moda Transportasi di Bnadara Radin Inten II - Bralinza, Chelpa Rideanda; Sulstyorini, Rahayu; Herianto, Dwi (Universitas Lampung, 2019)
The Indonesian government is increasingly active in improving the country's infrastructure, one of which is in the transportation sector. In 2016 the number of passengers of Radin Inten II Airport was 1.9 million after Radin Inten II Airport renovated on the side of the air and land side section number of passengers increased to 2.4 million passengers in 2017. If this continues, there will be a queue at the entrance and drop area zone.Data collection in this study was conducted in 2 stages. First, conducting a survey of vehicles at the entrance and exit of the airport for 14 hours, namely at 06:00 until 21:00, then the hand out the questionnaires in the waiting room and surveys in the drop zone area that is useful as supporting data. This study analyzes the characteristics of parking. Parking characteristics consist of parking time, parking duration, parking accumulation, parking usage level (PTO), parking capacity, parking indexThe study results show that in 2018 the Radin Inten II Airport parking lot is capable of accommodating all vehicles.